The Economics of "Bills Preferably" - Young, Ralph A.; Yager, Charles A. (Quarterly Journal of Economics, 1960)
Scope of paper, 341. — Any open market policy hinges on a well-performing government securities market, 342. — How the market facilitates monetary policy, 351. — Why monetary policy prefers short-term securities, 358. — Open market operations for other objectives, 363. — Concluding observations, 371.